Factors Associated With COVID-19 Non-vaccination in Adolescents Hospitalized Without COVID-19. Issue 1 (30th October 2022) - Sahni, Leila C; Price, Ashley M; Olson, Samantha M; Newhams, Margaret M; Pannaraj, Pia S; Maddux, Aline B; Halasa, Natasha B; Bline, Katherine E; Cameron, Melissa A; Schwartz, Stephanie P; Walker, Tracie C; Irby, Katherine; et al.
Abstract: Background: Pfizer-BioNTech COVID-19 vaccine received emergency use authorization for persons ≥ 16 years in December 2020 and for adolescents 12–15 years in May 2021. Despite the clear benefits and favorable safety profile, vaccine uptake in adolescents has been suboptimal. We sought to assess factors associated with COVID-19 non-vaccination in adolescents 12–18 years of age. Methods: Between June 1, 2021 and April 29, 2022, we assessed factors associated with COVID-19 non-vaccination in hospitalized adolescents ages 12–18 years enrolled in the Overcoming COVID-19 vaccine effectiveness network. Demographic characteristics and clinical information were captured through parent interviews and/or electronic medical record abstraction; COVID-19 vaccination was assessed through documented sources. We assessed associations between receipt of the COVID-19 vaccine and demographic and clinical factors using univariate and multivariable logistic regression and estimated adjusted odds ratios (aOR) for each factor associated with non-vaccination. Results: Among 1665 hospitalized adolescents without COVID-19, 56% were unvaccinated. Unvaccinated adolescents were younger (median age 15.1 years vs. 15.4 years, p < .01) and resided in areas with higher social vulnerability index (SVI) scores (median 0.6 vs 0.5, p < .001) than vaccinated adolescents. Residence in the Midwest [aOR 2.60 (95% CI: 1.80, 3.79)] or South [aOR 2.49 (95% CI: 1.77, 3.54)] US census regions, rarely or never receiving influenza vaccine [aOR 5.31 (95% CI: 3.81, 7.47)], and rarely or never taking precautions against COVID-19 [aOR 3.17 (95% CI: 1.94, 5.31)] were associated with non-vaccination against COVID-19. Conclusions: Efforts to increase COVID-19 vaccination of adolescents should focus on persons with geographic, socioeconomic, and medical risk factors associated with non-vaccination.